1998
DOI: 10.1038/sj.cdd.4400426
|View full text |Cite
|
Sign up to set email alerts
|

Increased spontaneous in vitro apoptosis in double negative T cells of humans with a fas/apo-1 mutation

Abstract: We describe a 17 year old patient suffering from Canale-Smith syndrome (CSS) including chronic lymphadenopathy, splenomegaly, hypergammaglobulinemia and recurrent Coombs positive hemolytic crises. The parents are not consanguine, all other family members including two brothers are healthy. Peripheral blood mononuclear cells of the patient showed an increased rate of CD3 positive, CD4/CD8 double negative T-lymphocytes. In vitro assays showed these cells to have an increased rate of spontaneous apoptosis. Though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…In a limited series of patients with lymphoproliferative disorders associated with Sjö gren's syndrome or type II mixed cryoglobulinemia, no CD95 germline mutations were apparently detected, but only four of the nine exons coding for the gene were analysed. 24 Autoimmune disorders with variable patterns of clinical features can be associated with germline CD95 mutations, 25,26 hence, it might be suggested that lymphomas arising in these patients might be more frequently associated with CD95 mutations. Our results do not confirm the association of CD95 mutations with extranodal lymphomas, and a pathogenic role of CD95 mutations might be limited to the human lymphoproliferative syndrome associated with autoimmune manifestations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a limited series of patients with lymphoproliferative disorders associated with Sjö gren's syndrome or type II mixed cryoglobulinemia, no CD95 germline mutations were apparently detected, but only four of the nine exons coding for the gene were analysed. 24 Autoimmune disorders with variable patterns of clinical features can be associated with germline CD95 mutations, 25,26 hence, it might be suggested that lymphomas arising in these patients might be more frequently associated with CD95 mutations. Our results do not confirm the association of CD95 mutations with extranodal lymphomas, and a pathogenic role of CD95 mutations might be limited to the human lymphoproliferative syndrome associated with autoimmune manifestations.…”
Section: Resultsmentioning
confidence: 99%
“…Our results do not confirm the association of CD95 mutations with extranodal lymphomas, and a pathogenic role of CD95 mutations might be limited to the human lymphoproliferative syndrome associated with autoimmune manifestations. [25][26][27] In fact, in marginal zone lymphomas, especially in the extranodal MALT type subset, other anti-apoptosis mechanisms seem to be present and are likely to be more relevant, such as the recently reported fusion protein AP12/MLT determined by the recurrent t(11;18)(q21;q21) chromosomal translocation, which can be detected in approximately one third of the cases of extranodal marginal zone lymphoma. 28 Indeed, the rearrangement of the apoptosis inhibitor gene API-2 may result in a survival advantage for the lymphoma B cell clones.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Death and Differentiation IL-2 deprivation-induced apoptosis independent of CD95 T Hieronymus et al since we could show increased spontaneous in vitro apoptosis of CD4 + , CD8 + and CD4 7 CD8 7 (double negative) T cells in the patients with the fas mutation, 29 our results of enhanced cleavage activities for some of the used caspase substrates in the lysates from one of these patients might argue for compensatory, CD95-independent pathways leading to apoptotic cell death in those patients. To point out the role of specific caspases in our model the expression of caspase-8, caspase-3 and the expression of PARP as a known substrate of caspase-3 in activated peripheral human T lymphocytes after IL-2 withdrawal were analyzed.…”
Section: Il-2 Deprivation-induced Apoptosis Independent Of Cd95mentioning
confidence: 99%
“…The fas gene mutations in these patients lead to an amino acid exchange at position 268 from glutamine to prolin but do not affect normal surface expression of CD95. 29 After extensive washing PHA blasts were incubated with 1 U/ml IL-2 in the presence or absence of 1 mg/ml of the apoptosis-inducing anti-Fas mAb or left unstimulated as indicated (Figure 2A). Cytokine deprivation-and Fasmediated induction of apoptosis was measured after 24 h. The data shown in Figure 2A indicate that the fas mutation abrogates the ability of the anti-Fas mAb to induce apoptosis in PHA blasts from these individuals, whereas PHA blasts were generated as described in Materials and Methods.…”
Section: Pha Blasts Are Susceptible To Fas-mediated and Il-2 Withdrawmentioning
confidence: 99%
“…FAS (CD95) and FAS-ligand interaction are associated with the induction of apoptosis (7). Stimulation of autoreactive B cells with anti-CD40 leads to an increase of FAS mediated apoptosis in vitro (8).…”
Section: Introductionmentioning
confidence: 99%